Promoting diverse communities of wild bees and hoverflies requires a landscape approach to managing meadows - Meyer, S.; Unternährer, D.; Arlettaz, R.; Humbert, J.; Menz, Myles (Elsevier BV, 2017)
© 2017 Elsevier B.V.There is ongoing concern regarding the observed decline in pollinator populations. Managing agricultural landscapes through agri-environment schemes (AES) supports biodiversity and could counteract pollinator population declines. We investigated whether alterations to current AES grassland mowing regimes would increase the abundance and species richness of wild bees and hoverflies. Furthermore, we investigated the response of different nesting and feeding guilds of wild bees and hoverflies, respectively, to these regimes. The three experimental mowing regimes were: (i) first cut not before 15 June, before the beginning of summer (Swiss AES management, control meadows); (ii) first cut delayed until 15 July (delayed meadows); (iii) as for control meadows but leaving 10–20% uncut as a refuge (refuge meadows). The rationale behind the delayed and refuge mowing regimes was extending the availability of floral resources for pollinators, while also providing refugia for species that may be directly impacted by mowing. Hoverflies and wild bees were collected in 2014 and 2015, respectively, using pan-trapping and sweep-netting, once before and once after the first cut. The two collecting methods showed contrasting results. While there was no difference in the abundance or richness of wild bees between the meadows when using pan traps, following the first cut, sweep-netting resulted in a higher abundance and richness of wild bees in delayed and refuge meadows compared to control meadows. Pan-trapping detected a higher abundance of hoverflies in delayed compared to refuge meadows, whereas sweep-netting detected a higher abundance in delayed and refuge compared to control meadows, after the first cut. Saprophagous hoverflies were more abundant in the control and delayed than refuge meadows following the first cut, when sampled with pan traps. Predatory hoverflies were more abundant and species rich in delayed and refuge compared to control meadows following the first cut, when sampled by sweep-netting. Our study demonstrates that simple alterations to a common AES grassland mowing regime can enhance populations of pollinators and natural enemies of crop pests. Furthermore, the contrasting response of the life-history guilds indicates that promoting heterogeneous management practices within the landscape is important for supporting diverse communities, and maintaining key ecosystem services such as pollination and biocontrol.